PELATIHAN PENELITIAN TINDAKAN KELAS DI SEKOLAH MENENGAH TEOLOGI KRISTEN WAIKABUBAK - Ezra Tari; Hendrik A.E Lao; Lanny I.D Koroh; Martin Ch. Liufeto (LPPM Universitas Abdurrab, 2022)
Selection of research topics Classroom action is significant for teachers. Because as part of the duties and responsibilities of teachers. This is important to support the teacher's career path to a higher rank. CAR is vital for improving the learning process. The method of devotion uses qualitative. Teachers can understand and are enthusiastic about writing down the results of learning improvements. The teacher learns how to make articles found to work well. Assistance continues with communication via WhatsApp.